Enhancing The Mathematical Communication Ability and Self-confidence of Junior High School Students Using Brain-Based Learning - Sri Solihah; Heris Hendriana; Rippi Maya (MEJ (Mathematics Education Journal), 2018)
This research is motivated by the fact shows the mathematicalcommunication ability of the students not yet in accordance with theexpected. One such problem is learning that does not provide flexibility tostudents to exploit the potential of the brain optimally, where in general isgenerally more emphasis on the left brain function. Mathematicalcommunication skills need to be supported by right brain function.Characteristics of learning that offers learning concepts that align the waythe brain works naturally designed is by learning Brain-Based Learning(BBL). The research method used is quasi experiment. Quantitative data isobtained from pretest and posttes data. Research found that There areachievements and improvements in students' mathematical communicationskills whose learning uses the Brain-Based Learning approach comparedwith students who received conventional learning in terms of students' earlymath skills, and self-confidence and there is an association between theability of mathematical communication and self-confidence.